Tinjauan Teoritis Tentang Migrasi Sistem Informasi Akuntansi Pendekatan Relasional ke Pendekatan Objek - Weli Weli (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2006)
The object-oriented approach in system design and development is gaining popularity. Some literature in information systems demonstrate that object-oriented approach is viewed as superior to conventional system development such as relational database approach. There were many advantages of object-oriented approach such as easier modeling, more efficient model reuse and more convenient maintenance.In this paper we introduce you to object-oriented design for Accounting Information Systems by migrate the relational approach to object-oriented approach based on Entity Relationship and REA diagram for revenue cycle.Keywords: ER Diagram, REA Model, object oriented design, terminologi, karakteristik.